When we are seen : how to come into your power--and empower others along the way - Young, Denise, 1955- (Crown, 2024)
"From one of the first and few women of color to reach the c-suite in Silicon Valley, Apple's former chief of HR, co-creator of the Apple Store culture, and first VP of inclusion and diversity, comes a heartfelt story of growing up Black and female in a world with little regard for either and a practical road map for embodying the best in yourself and emboldening others along the way. For her work as a co-creator of the Apple Store cultural experience, Denise Young has been deemed by leadership experts as one of the most emotionally intelligent leaders of her era. In this stirring narrative, part-memoir, part blueprint for action, she shares her vision of what it means to be truly seen at our places of work. As a "first and only" woman of color in boardrooms and leading roles across the Bay Area's booming tech industry, Denise was a trailblazer in a business that was never built for her. The first black and female senior executive under both Steve Jobs and Tim Cook, Denise was often in "the room where it happened." But within a white male-centric professional culture, she still had to work harder, smarter, and differently to get heard. She speaks candidly to that experience in these pages, offering lessons to those coming up behind her. In When We Are Seen, Denise shares insights on using your own story, empathy, intuition, and more to unlock the potential in yourself and others. Her story serves as both solace and strategy for anyone who has ever felt left out, unseen, ostracized; anyone who has been an only or a first. This is a book for anyone interested in upending perpetual cycles of exclusion, and in reclaiming our individual agency in the ongoing quest to thrive and belong. Denise argues that bringing your truest self to work-from wearing your beloved locs to sharing your artistic passion-and, in turn, holistically seeing the attributes others have to offer is not a passive experience; it is a specific skill we can and should build. And the result is a deeper understanding of what it means to be inclusive, and powerfully human on the job"--